Two Kartvelological Sessions at the World Congress in Medieval Studies - Irma Makaradze (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2026)
The World Congress in Medieval Studies took place in Leeds (UK) from July 5-9, 2015. This World Congress is traditionally of worldwide importance in Europe. Over 2400 delegates from different academic or research institutions attended the 22nd annual International Medieval Congress at the University of Leeds this year. It was the first time when those two Kartvelological sessions worked at the World Congress. It should also be noted that both Kartvelological sections, at the initiative of foreign colleagues, were organized by Professor Elguja Khintibidze.